Effectiveness of Mangosteen Peel Extract Garcinia mangostana in Inhibiting Aeromonas hydrophila Bacteria - Muahiddah, Nuri; Azhar, Fariq; Rachmat Scabra , Andre; Idris Affandi, Rangga; Dwiyanti , Septiana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The aquaculture sector is growing rapidly, but it faces various challenges, particularly concerning the health of fish and other aquatic organisms.This study aims to evaluate the potential of mangosteen peel extract as an antimicrobial agent against the bacterium Aeromonas hydrophila. This bacterium is known as a pathogen in fish and can cause significant diseases in aquaculture. Mangosteen peel extract was chosen because it contains active compounds such as xanthones, which have been proven to have antimicrobial properties. The initial method involves extraction with methanol, followed by filtration and separation using an evaporator. The method used to determine the content of mangosteen peel extract is FTIR analysis. Next, the antibacterial activity of the crude mangosteen peel extract is tested. The antioxidant testing is based on the agar diffusion method. Aeromonas hydrophila bacteria are cultured at a tested LD50 density of 0.05 ml on a TSA plate medium, spread evenly across the entire agar surface with a glass stick. Paper discs with a diameter of 6 mm, previously dipped in crude mangosteen peel extract, are placed on different TSA media. The test is repeated three times (triplicate) to obtain the average inhibition zone (clear zone), then incubated at 29°C, and observations are made of the inhibition zone's development at the 24th hour. The inhibition zone of mangosteen peel extract (Garcinia mangostana) against Aeromonas hydrophila bacteria, measuring 0.2±0.0 cm (20 mm), falls into the category of very strong. This indicates that mangosteen peel has the potential to be used as an alternative immunostimulant in place of antibiotics for the control of Motile Aeromonas Septicemia.